2010
DOI: 10.1111/j.1525-1446.2009.00821.x
|View full text |Cite
|
Sign up to set email alerts
|

Health and Safety Needs in Early Care and Education Programs: What do Directors, Child Health Records, and National Standards Tell Us?

Abstract: Comprehensive, multimethod assessments are useful to identify health and safety needs and develop public health nursing interventions for ECE programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The literature suggested that HH competence is influence by a myriad of factors such as beliefs, attitudes, motivational factors, awareness and the work environment (Alkon et al. ; Kelcikova et al. 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggested that HH competence is influence by a myriad of factors such as beliefs, attitudes, motivational factors, awareness and the work environment (Alkon et al. ; Kelcikova et al. 2012).…”
Section: Discussionmentioning
confidence: 99%
“…131 Children who attend child care facilities of poor quality receive less of the individualized attention that is necessary for healthy development, and they incur increased risk of exposure to multiple communicable diseases and a variety of potential injury hazards, including unsafe playground surfaces and equipment, missing or broken child safety gates, unattended windowblind cords, and a variety of equipment (such as cribs and bedding) and toys that do not meet current safety codes. 132 In the absence of national standards for monitoring the quality of the child care environment, each state currently formulates its own regulations and criteria. Although some guidance is available from professional organizations, such as the American Academy of Pediatrics' National Health and Safety Performance Standards, 133 widespread deficiencies in this highly fragmented diversity of settings are well known to child care directors and program staff.…”
Section: Policies and Programs That Assure Safe And Supportive Chemicmentioning
confidence: 99%
“…Among these practices, hand-washing and nappy-changing deserve the most attention (Alkon et al, 2009). Directors and observers of childcare centres have often witnessed the improper hand-washing practices of toddlers and staff (Alkon et al, 2010;Cassidy, et al,2004). For example, teachers generally wash their hands only after changing nappies or using the toilet.…”
Section: Health Practicesmentioning
confidence: 99%